Optimization of Insurance Brokerage Institutions in Realizing the Trust of the Indonesian Community - Gultom, Elisatris; Rohani, Siti; Disyon, Huta (Universitas Airlangga, 2024)
Public trust in the Indonesian insurance business is shaken by the crisis that rocked multiple insurance companies. This study investigates insurance brokerage institutions’ involvement in Indonesia’s insurance activities and how to improve public trust. This research uses normative legal research by examining library materials or secondary data. In contrast, the nature of the research is analytically descriptive, depicting the existence of insurance brokerage institutions in the Indonesian insurance industry for further analysis to complete the picture of brokerage companies’ role in improving the industry. The research found that insurance brokers help insureds choose an insurance carrier, handle the claims process, and resolve claim disputes, making them crucial to Indonesian insurance. Brokers can gain public trust by increasing insurance literacy, transparency of insurance product information, helping consumers resolve insurance claims and advising the Financial Services Authority on insurance regulations. To gain public trust in insurance, the insurance industry should prepare a more effective and comprehensive set of regulations to prevent legal uncertainty and provide adequate legal protection to customers. At a micro level, every regulation prepared by the company can provide certainty. The company’s ethics and corporate governance policy is explicit.